Trajectories and mishaps to care work in nursing: gender questions - Batista Andrade, Cristiane; Giovanelli Vedovato, Tatiana; Monteiro, Inês (Revista Punto Género, 2023)
Objective: To analyze the training and work trajectories of nursing technicians from a gender perspective, especially the sexual division of labor (STD). Methodology: Qualitative research in a large Brazilian city, with the use of oral history to understand work and training paths, reasons and choices for entering the profession. Interviews were conducted with eleven nursing technicians (nine women and two men). Results: Entry into the profession is motivated by obtaining a job; improvement in salary conditions for men and women; desire to care related to “vocation” and family influence. Some women have had interruptions due to reproductive work; the discontinuities in the trajectories were not experienced by men and by young women without children. Conclusions: The STD approach allowed us to understand the different pathways for care work between genders, the reasons for career and work interruptions